2009
DOI: 10.1897/08-191.1
|View full text |Cite
|
Sign up to set email alerts
|

Pulp and paper mill effluent treatments have differential endocrine‐disrupting effects on rainbow trout

Abstract: Endocrine disruption (ED) effects due to pulp and paper mill effluents extracts involving different industrial procedures and effluent treatments (nontreated, primary, and secondary treated) were evaluated using immature triploid rainbow trout in a pulse-exposure toxicity experiment. The protocol involved the use of intraperitoneal injection of mill extracts (solid-phase extraction [SPE]) corrected for individual fish weight and included several laboratory standards (steroidal hormones and phytosterols). Biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 41 publications
4
48
0
Order By: Relevance
“…The positive feedback mechanism triggered by steroidal hormones from the ovary acts on the liver to produce VTG, which increases plasma VTG concentrations. However, there is a time delay between the induction of VTG production and physiological growth in the gonadal tissue as the oocytes absorb the protein [28]. Fish 2, 6 and 7 all had similar average GSI's with medium to low VTG concentrations in their blood plasma and the majority of oocytes in the immature stages.…”
Section: Relating Gsi Plasma Vtg and Gonad Developmentmentioning
confidence: 99%
“…The positive feedback mechanism triggered by steroidal hormones from the ovary acts on the liver to produce VTG, which increases plasma VTG concentrations. However, there is a time delay between the induction of VTG production and physiological growth in the gonadal tissue as the oocytes absorb the protein [28]. Fish 2, 6 and 7 all had similar average GSI's with medium to low VTG concentrations in their blood plasma and the majority of oocytes in the immature stages.…”
Section: Relating Gsi Plasma Vtg and Gonad Developmentmentioning
confidence: 99%
“…Nevertheless, other inputs of vascular plant phytosterols into coastal waters may come from upland forests, mangroves, oil palm, or coconut plantations (Ali et al, 2009), waste waters (Quemeneur & Marty, 1994;Liu et al, 2010) and the pulp and paper mill industry (Owens, 1991;Sepúlveda et al, 2003;Orrego et al, 2005aOrrego et al, , 2009). Important research efforts has been undertaken to evaluate the impact of the discharge of pulp mill effluents on fish reproductive behavior (e.g., Walker et al, 2002;Dubé et al, 2008), because it has been shown that fishes exposed to wood-derived sterols present endocrine disruption (Mellanen et al, 1996;MacLatchy et al, 1997;Nakari & Erkomaa, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Bertin et al (2011) recently showed remarkably high levels of 17α-ethinylestradiol in coastal sediments, enough to cause endocrine disorders in fish inhabiting some of the aquatic ecosystems of this region. In addition, several studies have shown endocrine-disrupting effects in caged rainbow trout located downstream from pulp mill discharges in the BioBío River (Orrego et al, 2005a(Orrego et al, , 2006(Orrego et al, , 2009. There is an important production of cellulose in south-central Chile of about 3.32 million ton annually; accordingly, phytosterols derived from this activity are incorporated into aquatic systems.…”
Section: Introductionmentioning
confidence: 99%
“…1 The generation of effluents from the production of cellulose, affects mainly to the Central Southern zone, in the Biobío basin region and have identified as a potential source of endocrinal activity in the receiving water bodies [2][3][4] due to the presence, among others, of wood extractives such as fatty acids, sterols, phenolic compounds and terpenes (di and triterpenes are emphasized). 5,6 Investigations carried out intended to recognize its real dimension are scarce but in constant development.…”
Section: Introductionmentioning
confidence: 99%
“…2,7 This kind of compounds can cause physiological abnormalities 1,5,8 or even morphological. 3 Orrego et al 7,9 stated an increased size and precocious gonad maturity in females as well as an increase in the plasmatic vitelogenine in juvenile males of Oncorhynchus mykiss exposed to sediments influenced by effluents derived from the cellulose production in the Biobío River. Similarly, the intraperitoneal injection of extracts obtained by means of SPE to treated effluents reaffirmed what it was previously reported.…”
Section: Introductionmentioning
confidence: 99%